NILAI KEARIFAN LOKAL BUGIS MAKASSAR DALAM CERPEN PANGGIL AKU AISYAH KARYA THAMRIN PAELORI - Sitti Aida Azis (JURNAL KONFIKS, 2017)
The purpose of research is to describe the values of local wisdom short story "Panggil Aku Aisyah" written by Thamrin Paelori. This research is in the form of qualitative descriptive that is expose and submit data objectively the values of local wisdom. The data in the study are: mutual respect (sipakatau), reminding each other (sipakainge), mutual respect (sipakalebbi). The data source is short story "Panggil Aku Aisyah" by Thamrin Paelori, first print. Based on the research results revealed that, respect for each other (sipakatau), is the human nature, which is looking at human beings not in terms of culture, race, religion and social status, remind each other (Sipakainge), is a mutual nature remind. Born as a human being is inseparable from a mistake and an oversight. Thus human beings should remind each other that no human being is perfectly born even though man is God's most perfect and deficient creation that will perfect man. Mutual respect (Sipakalebbi), reminds that humans are full of deficiencies and advantages, and need others, therefore, if there deficiency not be a measure and still see that humans there are advantages